Paper Stories - Paper and Book History in Early Modern Europe - Hufnagel, Silvia; Sigurðardóttir, Þórunn; Ólafsson, Davíð (Materiale Textkulturen, 2023)
This book examines paper and material aspects of the written word in early modern Europe. The contributors investigate the origins of paper production as well as manufacture, use, ownership, trade and preservation of books. This interdisciplinary volume brings together the research of paper experts, book historians, philologists, conservators and specialists in watermark analysis, paper trade, the history of collections and object biography.